A Synthetic Cycle for Nitrogen Atom Transfer Featuring a Diruthenium Nitride Intermediate. Issue 22 (17th April 2013) - Corcos, Amanda R.; Long, Amanda Kae Musch; Guzei, Ilia A.; Berry, John F.
Abstract: A new Ru2 azido complex, [Ru2 (chp)4 N3 ] (4, chp = 2‐chloro‐6‐hydroxypyridinate), was investigated under photolytic conditions to study the chemical reactivity of the corresponding Ru2 nitride species, [Ru2 (chp)4 N] (6 ), towards intermolecular N atom transfer to triphenylphosphane (PPh3 ). Photolysis of a dichloromethane solution of4 at λ > 350 nm leads to a characteristic color change from purple to magenta. Upon acidic workup, triphenylphosphanamine chloride ([H2 NPPh3 ]Cl) is produced and [Ru2 (chp)4 Cl] (5 ), the precursor to4, is regenerated. The first stoichiometric cycle for intermolecular N atom transfer from a Ru2 nitride is thus presented. Abstract : The new Ru2 azido complex [Ru2 (chp)4 N3 ] (chp = 2‐chloro‐6‐hydroxypyridinate) reacts with PPh3 under photolytic conditions to form [H2 NPPh3 ] + Cl – and [Ru2 (chp)4 Cl], from which the azide complex can be regenerated.